Molecular identification of tick-borne hemoparasites in equines from Northwestern Colombia - Yeison Agudelo-Ruíz (Revista MVZ Córdoba, 2017)
Objective. To detect and identify Anaplasmataceae agents and piroplasms in equines from the slaughterhouse “La Rinconada” at Rionegro municipality in Antioquia. Materials and methods. A descriptive cross-sectional study was carried out on equines selected by convenience during a period of 2015. Information about species, sex, age and origin of the animals. Whole blood was collected for DNA extraction procedure, and a PCR targeting a 360bp of Anaplasmataceae 16S ribosomal gene and 450bp of 18S ribosomal gene of Piroplasm were used for detection. PCR amplicons selected were submitted to direct sequencing for identification of hemoparasites through genetic analysis Results.135 equine samples from Antioquia, Cordoba y Sucre were analyzed. 78% were horses, 16% were donkeys and 6% were mules. Anaplasmataceae agents were not detected in any sample, meanwhile 13% were positive to piroplasm PCR. Sequence analysis reveals the circulation of Theileria equi in northwestern Colombia. Conclusions. This work presents the first molecular evidence of at least three genotypes of T. equi in equines of northwestern Colombia.